Vampires, dragons, and Egyptian kings youth gangs in postwar New York - Schneider, Eric C. 1951-2017 (Princeton Univ. Press, 1999)
They called themselves "Vampires" "Dragons" and "Egyptian Kings".They were divided by race, ethnicity, and neighborhood boundaries, but united by common styles, slang, and codes of honor. They fought-and sometimes killed-to protect and expand their territories. In postwar New York, youth gangs were a colorful and controversial part of the urban landscape, made famous by West Side Story and infamous by the media. This is the first historical study to explore fully the culture of these gangs. Schneider takes us into a world of switchblades and slums, zoot suits and bebop music to explain why youth gangs emerged, how they evolved, and why young men found membership and the violence it involved so attractive. He begins by describing how postwar urban renewal, slum clearances, and ethnic migration pitted African-American, Puerto Rican, and Euro-American youths against each other in battles to dominate changing neighborhoods. But he argues that young men ultimately joined gangs less because of ethnicity than because membership and gang violence offered rare opportunities for adolescents alienated from school, work, or the family to win prestige, power, adulation from girls, and a masculine identity. In the course of the book, Schneider paints a rich and detailed portrait of everyday life in gangs, drawing on personal interviews with former members to re-create for us their language, music, clothing, and social mores. He outlines the unwritten rules of gang behavior, the paths members followed to adulthood, and the effects of gang intervention programs, while also providing detailed analyses of such notorious gang-related crimes as the murders committed by the "Capeman" Salvador Agron. Schneider focuses on the years 1940-1975, but takes us up to the present in his conclusion, showing how youth gangs are no longer social organizations but economic units tied to the underground economy.
Keywords: Geschichte 1900-2000; Geschichte 1945-1999; Gangs - New York (État) - New York - Histoire - 20e siècle; Jeugdbenden; Geschichte; Gangs -- New York (State) -- New York -- History -- 20th century; Jugendkriminalität; Jugendbande; New York, NY